Build Digital Business Planning Online Market Apps Application based Traditional Markets Online - Pangestu, Aldi Putra; Malinda, Maya (Proceedings International Conference on Education Innovation and Social Science, 2023)
Traditional markets are places to shop for various kinds of vegetables and household needs. The background of this journal is that there is a lot of pollution around traditional markets, such as water, air, noise pollution and congestion around traditional markets. The purpose of the presence of OMA (Online Market Apps) is to reduce pollution around traditional markets, besides that it is efficient for a buyer because he can make transactions via a smartphone. With OMA, this application targets young people who want to shop easily and cheaply. The method used is literature review, there are many existing breakthroughs, but they are not efficient. The results of the OMA will increase convenience and reduce pollution and congestion around traditional markets. The limitation is the lack of further knowledge about parents' consumer interest in online shopping, compared to young people, young people prefer online shopping because it is more efficient and easier. The originality of this journal is that OMA provides convenience and has inexpensive selling prices. In addition, the OMA application has developed a payment system on the spot, but with the condition that you make a deposit first. With this convenience and efficiency as well as the ease of using the application, it is hoped that parents can use this application more easily.